Analysis of Challenges in Tour Guiding Within Protected Areas of Uganda: A Case Study of Bwindi Impenetrable National Park. - Ainebyona, Precious (Kabale University, 2024)
This study aimed to analyze the challenges facing tour guides in Protected areas using the case study of Bwindi Impenetrable National Park. Tour guiding is defined as where the tourist is given someone to escort and direct him throughout his or her trip to a certain destination. Tour guides are one of the most significant elements in the tourism industry. They inform, interpret, educate, interact, and communicate with tourists about the destination, its history, culture, local/host community, and the nature of the destination. Tour guiding within Bwindi Impenetrable National Park is faced with different challenges that hinder the seamless experience of tourists and jeopardize the preservation of this precious natural habitat. The objectives of the study were to find out challenges facing tour guiding within Bwindi Impenetrable National Park, to assess the causes of challenges facing tour guiding in Bwindi Impenetrable, and to suggest solutions to challenges facing tour guiding within the tourism industry in Bwindi National Park. A population of 200 respondents was targeted, however a sample size of 133 was used. Research methods that is questionnaire method were used The researcher constructed a relevant and straight-forward questionnaire for great ease of respondents’ understanding, interpretation and quicker feedback. The findings on challenges facing tour guiding within Bwindi Impenetrable National Park include poor infrastructure, lack of proper training, Language barriers, and Poor communication among stakeholders.